P843 Mucinous and signet-ring colonic adenocarcinoma in Inflammatory Bowel Disease. (30th January 2023) - Neri, B; Pizzi, F; Savino, L; Salvatori, S; Mossa, M; Lolli, E; Calabrese, E; Sica, G; Petruzziello, C; Monteleone, G; Biancone, L
Abstract: Background: Colorectal cancer (CRC) risk is increased in patients (pts) with long-standing colitis related to Inflammatory Bowel Disease (IBD). A higher frequency mucinous and signet-ring colonic adenocarcinoma has been suggested in IBD, but data regarding risk factors for these aggressive CRC are currently lacking. Primary aim was to assess the frequency of mucinous and signet-ring adenocarcinoma in IBD pts with CRC. Secondary aim was to assess risk factors for these histotypes of CRC. Methods: From January 2002 to July 2022, all IBD pts with concomitant CRC were retrospectively enrolled. Inclusion criteria: 1) age ≥18; 2) well-defined diagnosis of IBD and CRC; 3) available histological and surgical report. Exclusion criteria: Missing data. Characteristics of IBD were reported according to standard criteria. Data were expressed as median [range]. Student-t Test and χ2 test were used for comparisons. Univariate logistic regression model was applied for assessing risk factors for mucinous and signet-ring adenocarcinoma (OR [95%CI]). Results: The study population included 40 IBD pts with concomitant CRC: 24 (60%) with Ulcerative Colitis (UC) and 16 (40%) with Crohn's Disease (CD). CRC included standard adenocarcinoma in 23 (57.5%) and mucinous or signet-ring in 17 (42.5%) pts. CD was more frequently stricturing in pts with standard adenocarcinoma (7 [77.8%] vs 1 [14.4%], p=0.04). CRC most frequently involved the rectum in pts with mucinous or signet-ring adenocarcinoma vs standard adenocarcinoma (4 [17.4%] vs 8 [47.1%]; p=0.04). Other IBD characteristics did not differ between standard and mucinous or signet-ring adenocarcinoma, including: age at CRC diagnosis (61 [30-80] vs 53 [29.80]; p=0.61), gender (F): 8 [34.8%] vs 5 [29.4%]; p=0.98), IBD duration at CRC diagnosis (14 [1-45] vs 17 [1-36]; p=0.74), smoking status (p=0.78), IBD type (UC: 14 [60.9%] vs 9 [56.3%]; p=0.84), UC extent and CD localization, frequency of perianal disease (p=0.37), thiopurine (p=0.55) or biologic (p=0.55) use. The proportion of pts surgically treated for CRC (20 [86.9%] vs 17 [100%], p=0.34) and the frequency of CRC-related death (3 [13.1%] vs 5 [29.4%]; p=0.37) were also comparable between groups. At diagnosis, CRC stage was comparable between pts with standard vs mucinous or signet-ring adenocarcinoma (stage I: 6 [26.1%] vs 1 [5.9%]; p=0.21; II: 9 [39.1%] vs 4 [23.5%]; p=0.48; III: 5 [21.7%] vs 7 [41.2%]; p=0.34); IV: 3 [13.1%] vs 2 [11.8%]; p=0.71). At univariate analysis, no specific risk factors for mucinous and signet-ring colonic adenocarcinoma were detected. Conclusion: In the tested cohort of IBD patients with CRC, mucinous and signet-ring adenocarcinomas were observed in almost half of cases, although no specific risk factors were identified.